IKLAN LAYANAN MASYARAKAT ETIKA BERKOMUNIKASI MASYARAKAT MINANG DI SITUS JEJARING SOSIAL - ade moussadecq; Agung Eko BW; Rosta Minawati (Ranah Seni, 2018)
Surveys from APJII conducted in 2016, states 1.8 million or 35% of people in the province of West Sumatra have been connected to the Internet and often access social networking sites like Facebook and Twitter. The low ethics of social media of some people causes them to write down the status of SARA. In the Minangkabau community, known ethics communicate organize communications that are compatible with the morma and cultural values ​​of Minangkabau, namely "Kato nan Ampek" and Kaba. Because of the phenomenon related to the phenomenon of the low ethics of the Minangkabau community in social networking sites has inspired the writer's desire to design ILM in the form of motion graphic video that is persuasive in persuasive community to give normative ethics to communicate in the context of Minangkabau culture on social networking sites. The main media of ILM is motion graphic video and is supported with other media such as stickers that are mobile and facilitate the delivery of messages, banners to be published in strategic areas, pins as souvenirs and X banner as a media campaign for in door (inside the room).